Smoking prevalence and smoking cessation services for pregnant women in Scotland - Shipton Debbie; Eadie Douglas; Bauld Linda; MacAskill Susan; Tappin David M; Galbraith Linsey (BMC, 2010)
Abstract Background Over 20% of women smoke throughout pregnancy despite the known risks to mother and child. Engagement in face-to-face support is a good measure of service reach. The Scottish Government has set a target that by 2010 8% of smokers will have quit via NHS cessation services. At present less than 4% stop during pregnancy. We aimed to establish a denominator for pregnant smokers in Scotland and describe the proportion who are referred to specialist services, engage in one-to-one counselling, set a quit date and quit 4 weeks later. Methods This was a descriptive epidemiological study using routinely collected data supplemented by questionnaire information from specialist pregnancy cessation services. Results 13266 of 52370 (25%) pregnant women reported being current smokers at maternity booking and 3133/13266 (24%) were referred to specialist cessation services in 2005/6. Two main types of specialist smoking cessation support for pregnant women were in place in Scotland. The first involved identification using self-report and carbon monoxide breath test for all pregnant women with routine referral (1936/3352, 58% referred) to clinic based support (386, 11.5% engaged). 370 (11%) women set a quit date and 116 (3.5%) had quit 4 weeks later. The second involved identification by self report and referral of women who wanted help (1195/2776, 43% referred) for home based support (377/1954, 19% engaged). 409(15%) smokers set a quit date and 119 (4.3%) had quit 4 weeks later. Cost of home-based support was greater. In Scotland only 265/8062 (3.2%) pregnant smokers identified at maternity booking, living in areas with recognised specialist or good generic services, quit smoking during 2006. Conclusions In Scotland, a small proportion of pregnant smokers are supported to stop. Poor outcomes are a product of current limitations to each step of service provision - identification, referral, engagement and treatment. Many smokers are not asked about smoking at maternity booking or provide false information. Carbon monoxide breath testing can bypass this difficulty. Identified smokers may not be referred but an opt-out referral policy can remove this barrier. Engagement at home allowed a greater proportion to set a quit date and quit, but costs were higher.